ANALYSIS OF QUALITY OF SLEEP AND OUTCOMES IN MILD HEAD INJURY PATIENTS WITH OR WITHOUT RADIOLOGICAL FINDINGS - VIDHYAALAKSHMI, SUNDARARAAJAN; ANAND, VEERARAGHAVALU SUDHAKAR SATHISH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
INTRODUCTION: Primary cause of long-term or permanent trauma-related disability worldwide is traumatic brain injury (TBI), which is also a global health concern [1]. One of the most prevalent and immediate consequences of TBI is sleep disorders, which seriously impair patients' quality of life (QoL) and rehabilitation [2]. This retrospective study aims to evaluate the quality of sleep and its outcomes with or without radiological findings in ct brain in mild head trauma patients and also with clinical correlations and demographic correlations. METHODS: Retrospective observational study conducted by Saveetha Medical College during the period of July 2024 to March 2025. The inclusion criteria were only mild head injury patients with GCS>13/15, age>15yrs, non-operative patients and in patients Exclusion criteria included GCS <13/15, Pediatric age group and operated patients and out patients. Various parameters such as history, clinical signs, radiological findings, vitals were employed for assessing quality of sleep using sleep quality index. Software employed for statistical purposes was IBM SPSS software. RESULTS: Total of 100 patients were reported to the trauma centre during the period of the study. The male-to-female ratio was 1.08:1. Including all age groups, 72% (n-77) fell under mild sleep quality, others 23% (n-23) fell under moderate sleep quality category. Considering both sexes, 68% (n-34) had mild sleep quality index, rest 32% (n-16) had moderate sleep quality. Compared with GCS, Including all age groups, 86% fell under mild sleep quality, others 14% fell under moderate sleep quality category. With all Ct brain findings 68% (n-34) had mild sleep quality index, rest 32% (n-16) had moderate sleep quality. In ct brain normal findings patients, 92% (n-41 ) had mild sleep index index, rest 18%( n-9) had moderate sleep index index. All patients had stable vitals. None of the patients had severe sleep quality index. Thus it is concluded that 76% had mild sleep quality index and 24% had moderate sleep quality index and none had severe sleep quality index. CONCLUSION: CT BRAIN can be used as a triaging tool in mild head trauma. Sleep disturbances are a significant issue for many patients having mild head injuries and can contribute to the overall burden of the injury, impacting cognitive, emotional, and physical recovery. Thus Sleep quality index has been employed for assessing degree of severity of disturbances among these patients. Thus it can be concluded from the study that majority of the patients had minimal sleep disturbances and very few had some disturbances, however not affecting their quality of life.